INVESTIGATION OF ANAEROBIC AND AEROBIC DEGRADATION PROCESSES IN SANITARY LANDFILL - Top, Selin; Sekman, Elif; Yazici, Remziye; Demir, Ahmet; Bilgili, M. Sinan (YILDIZ TECHNICAL UNIV, 2011)
In this paper, leachate recirculation and aerobic landfilling of solid wastes investigated as alternative methods for enhancing solid waste stabilization in landfills. Four field scale landfill test cells which were constructed. Landfill with the dimensions of 20x40x5 m were used to determine the aerobic and anaerobic waste degradation processes. The landfilling options which were used in this study are conventional landfill (AN-1), anaerobic with leachate recirculation (AN-2), semi-aerobic landfill (A-1), and aerobic landfill (A-2). The results obtained during 250 days test cells are given. After the filling of solid wastes to test cells, the effects of these various methods on leachate quality, and temperature distributions in landfill body were determined. pH, chloride (Cl-), total alkalinity, chemical oxygen demand (COD), biological oxygen demand (BOD5), total Kjeldahl nitrogen (TKN), ammoniac nitrogen (NH3-N) parameters were conducted in leachate phase.
Keywords: Solid wastes; leachate recirculation; aerobic landfill; anaerobic landfill; Engineering